2008
DOI: 10.1016/j.cell.2008.11.015
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Phage T4 DNA Packaging Motor Suggests a Mechanism Dependent on Electrostatic Forces

Abstract: Viral genomes are packaged into "procapsids" by powerful molecular motors. We report the crystal structure of the DNA packaging motor protein, gene product 17 (gp17), in bacteriophage T4. The structure consists of an N-terminal ATPase domain, which provides energy for compacting DNA, and a C-terminal nuclease domain, which terminates packaging. We show that another function of the C-terminal domain is to translocate the genome into the procapsid. The two domains are in close contact in the crystal structure, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

27
495
8
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(531 citation statements)
references
References 53 publications
27
495
8
1
Order By: Relevance
“…Previous data suggested molecular interactions between terminase large subunits and portals in bacteriophages lambda (30), T3 (31), and T4 (32), and conserved polypeptide segments containing acidic and hydrophobic residues near the C termini of terminase large subunits of these three phages were identified to be potential portal-interacting sites. Direct contact between terminase large subunits and portal was also evident in an in vitro DNA-packaging system for phages T4 consisting of the terminase large subunit and the procapsid (7,33) and an intermediate resolution electron cryomicroscopic analysis of phi29 procapsid captured in the process of DNA-packaging (9). On the other hand, it was reported that the C-terminal region of phage lambda terminase small subunit gpNu1 (DNA-recognition component) was responsible for interaction with the terminase large subunit (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data suggested molecular interactions between terminase large subunits and portals in bacteriophages lambda (30), T3 (31), and T4 (32), and conserved polypeptide segments containing acidic and hydrophobic residues near the C termini of terminase large subunits of these three phages were identified to be potential portal-interacting sites. Direct contact between terminase large subunits and portal was also evident in an in vitro DNA-packaging system for phages T4 consisting of the terminase large subunit and the procapsid (7,33) and an intermediate resolution electron cryomicroscopic analysis of phi29 procapsid captured in the process of DNA-packaging (9). On the other hand, it was reported that the C-terminal region of phage lambda terminase small subunit gpNu1 (DNA-recognition component) was responsible for interaction with the terminase large subunit (23).…”
Section: Discussionmentioning
confidence: 99%
“…The terminase must dock onto the procapsid through association with the portal to start DNA translocation. Unlike sequence diversity in terminase small subunits, most phage terminase large subunits show conserved ATPase activity and nuclease activity associated with respective domains of the proteins, which is also true in herpesvirus (1,7). Previous data suggested molecular interactions between terminase large subunits and portals in bacteriophages lambda (30), T3 (31), and T4 (32), and conserved polypeptide segments containing acidic and hydrophobic residues near the C termini of terminase large subunits of these three phages were identified to be potential portal-interacting sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-resolution structures of all of the conserved motor components found among tailed dsDNA bacteriophages have been determined (2)(3)(4)(5). The small bacteriophage T4 terminase protein gp16 is required for cutting and packaging the replicative DNA concatemer in vivo but is nonessential and inhibitory for linear DNA packaging in vitro (6).…”
mentioning
confidence: 99%
“…Furthermore, bacteriophages provide enzymes for digesting bacterial cell walls, mechanical means for puncturing cell membranes, and a tube for delivering the DNA genome into the host cytoplasm. In addition, the special vertex may be required for genome packaging into preformed proheads, as in HSV (15) or in most bacteriophages (18,19). Yet another function of special vertices can be to nucleate prohead assembly in some bacteriophages (20).…”
mentioning
confidence: 99%